1996
DOI: 10.1577/1548-8659(1996)125<0645:avonit>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme Variability ofOncorhynchus nerkain the Pacific Northwest, with Special Consideration to Populations of Redfish Lake, Idaho

Abstract: We resolved allozyme variation among 28 enzymes encoded by 58 protein loci in 27 samples of sockeye salmon and kokanee Oncorhynchus nerka in the Pacific Northwest. Of 32 polymorphic loci, 16 were polymorphic at the P0.95 level (frequency of the common allele ≤0.95). We found substantial variation at mAAT‐1* and mAH‐1,2*, loci not previously described in O. nerka in this portion of its distribution. Mean heterozygosity per sample ranged from 0.010 to 0.036 and averaged 0.028 over all samples. Wrightˈs fixation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 0 publications
7
58
0
Order By: Relevance
“…When the H11 haplotype was included, 90% -100% of the kokanee samples were included, vs. 72% and 90% for the Okanogan and Shuswap sockeye samples, respectively. Similar results were observed by Winans et al (1996), who hypothesized that stream capture in recent geological time (the two river systems are less than 20 km apart) may have allowed gene flow, accounting for the genetic similarity between these sockeye and kokanee populations. Robison (1995) suggested that Shuswap Lake kokanee might have been transplanted to Okanogan Lake.…”
Section: Genetic Variation Of Sympatric O Nerka Populationssupporting
confidence: 84%
See 3 more Smart Citations
“…When the H11 haplotype was included, 90% -100% of the kokanee samples were included, vs. 72% and 90% for the Okanogan and Shuswap sockeye samples, respectively. Similar results were observed by Winans et al (1996), who hypothesized that stream capture in recent geological time (the two river systems are less than 20 km apart) may have allowed gene flow, accounting for the genetic similarity between these sockeye and kokanee populations. Robison (1995) suggested that Shuswap Lake kokanee might have been transplanted to Okanogan Lake.…”
Section: Genetic Variation Of Sympatric O Nerka Populationssupporting
confidence: 84%
“…Fish passage to Suttle Lake was subsequently blocked by installation of a dam and screen at the outlet in 1930 (Fulton 1970 Comparison of other Snake River kokanee populations sampled revealed a high degree of genetic similarity between Anderson Ranch Reservoir, Deadwood Reservoir, Dworshak Reservoir, and Payette Lake. Their similarity reflects the transfers of kokanee that occurred between these lake systems , Winans et al 1996.…”
Section: Genetic Variation Of Sympatric O Nerka Populationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Four sources of fish were initially used, but the early spawning strain from Anderson Ranch Reservoir, Idaho now populates the reservoir (Winans et al 1996). These fish spawn during September in tributary streams as far as 140 km above the reservoir.…”
Section: Description Of Study Areamentioning
confidence: 99%